2020
DOI: 10.3855/jidc.12600
|View full text |Cite
|
Sign up to set email alerts
|

Similarity in Case Fatality Rates (CFR) of COVID-19/SARS-COV-2 in Italy and China

Abstract: As of 28 February 2020, Italy had 888 cases of SARS-CoV-2 infections, with most cases in Northern Italy in the Lombardia and Veneto regions. Travel-related cases were the main source of COVID-19 cases during the early stages of the current epidemic in Italy. The month of February, however, has been dominated by two large clusters of outbreaks in Northern Italy, south of Milan, with mainly local transmission the source of infections. Contact tracing has failed to identify patient zero in one of the outbreaks. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
305
4
32

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(379 citation statements)
references
References 0 publications
23
305
4
32
Order By: Relevance
“…Several smaller cohort studies have yielded similar results suggesting higher risk for adverse events in patients with CVD who contract COVID-19, although biases related to testing and standardized data apply here as well (1,19,(25)(26)(27)(28). Notably, while reports outside of China are limited, data from Italy suggest similar mortality rates and an elevated risk for death in patients with comorbidities (29). As emerging international data become available, analysis from multinational cohorts can help inform risk stratification for severe disease especially for patients with prior CVD.…”
Section: Prevalence Of Cvd In Patients With Covid-19supporting
confidence: 52%
“…Several smaller cohort studies have yielded similar results suggesting higher risk for adverse events in patients with CVD who contract COVID-19, although biases related to testing and standardized data apply here as well (1,19,(25)(26)(27)(28). Notably, while reports outside of China are limited, data from Italy suggest similar mortality rates and an elevated risk for death in patients with comorbidities (29). As emerging international data become available, analysis from multinational cohorts can help inform risk stratification for severe disease especially for patients with prior CVD.…”
Section: Prevalence Of Cvd In Patients With Covid-19supporting
confidence: 52%
“…In this context, Latin America was the last significant region where COVID-19 arrived [27,40]. In this case, coming mainly from two European countries, Italy and Spain [18][19][20][21][22]. In Bolivia, the first two cases came from Italy.…”
Section: Discussionmentioning
confidence: 99%
“…After its zoonotic emergence in China, during November-December 2019 [1][2][3][4][5][6][7][8], the Coronavirus Disease 2019 (COVID- 19), caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) [9], spread significantly into other countries in Asia [10][11][12][13][14]. Then, to other continents such as the Pacific region [15], North America [16,17], Europe [18][19][20][21][22], and even Africa [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…(6) Of patients with myocardial injury, prognosis is particularly poor for those with a prior history of CVD. (7) Across nations, studies have also consistently demonstrated significantly higher case fatality rates in older persons (8)(9)(10)(11)(12), which may reflect an increased prevalence of comorbid conditions, as well as age-related declines in T-cell and B-cell function. (13) While the current literature does not yet include specific descriptions of the impact of COVID-19 in patients with structural heart disease (SHD), it is reasonable to extrapolate that these patients are high risk for adverse outcomes based on their advanced age and numerous comorbidities.…”
Section: Implications Of Covid-19 For Patients With Structural Heart mentioning
confidence: 99%